Contracting and Sector Choice across Municipal Services - Feiock, Richard C.; Clinger, James C.; Shrestha, Manoj; Dasse, Carl (State & local government review, 2007)
Whether organizations should contract out for goods and services or produce them internally continues to be a subject of debate. Service contracting patterns in cities may be explained by the characteristics of goods and services and the extent of political and administrative uncertainty in city leadership. Turnover in executive leadership can affect the ability of local governments to negotiate contracts, make credible commitments to suppliers, and faithfully uphold and enforce contracts. When transaction costs resulting from turnover are high, contracting out becomes less likely. The results of this study show that both city manager turnover and certain service types significantly reduce the likelihood of service contracting, particularly with private, for-profit providers.